Reading between the vines: Hosts as islands for extreme holoparasitic plants. Issue 9 (12th September 2017) - Barkman, Todd J.; Klooster, Matthew R.; Gaddis, Keith D.; Franzone, Brian; Calhoun, Sondra; Manickam, Sugumaran; Vessabutr, Suyanee; Sasirat, Sawitree; Davis, Charles C.
Abstract : PREMISE OF THE STUDY: Partitioning of population genetic variation in plants may be affected by numerous factors including life history and dispersal characteristics. In parasitic plants, interactions with host populations may be an additional factor influencing partitioning. To test for hierarchical population genetic patterns related to obligate endoparasitism, we studied three species of Rafflesiaceae, which grow as extremely reduced endophytes infecting Tetrastigma vines in Southeast Asia. METHODS: Microsatellite markers were developed and multilocus genotypes were determined for Rafflesia cantleyi, Rafflesia tuan‐mudae, and Sapria himalayana and each of their Tetrastigma hosts. Relatedness among parasite individuals was estimated, and AMOVAs were used to determine levels of population genetic subdivision. KEY RESULTS: Microsatellite genotypes for 340 paired parasite and host samples revealed that host vines were infected by numerous Rafflesiaceae individuals that may spread for up to 14 m within stem tissues. Surprisingly, Rafflesiaceae parasites within a given host are significantly more closely related to each other than individuals of the same species in other host individuals. The pattern of hierarchical population genetic subdivision we detected across species is likely due to limited seed dispersal with reinfection of natal host vines. CONCLUSIONS: These findings demonstrate common population genetic patterns between animal and plant parasites, potentially indicating advantages of close relatives infecting hosts. This study also has important conservation implications for Rafflesiaceae since our data suggest that destruction of a single infected host vine could result in large genetic losses.